ADDITIONAL DATA ON THE GOLD HOARD FROM VÍZIVÁROS - Lajos Juhász (Journal of Ancient History and Archaeology)
The gold hoard found in 1994 in the Víziváros south of Aquincum was only briefly published by M. Torbágyi. The 9 aurei from Tiberius to Vespasian, closing in 71 AD were most likely hidden around the middle of the 70s. New data have since emerged on the find context make it likely that it was uncovered within the camp of the ala I Hispanorum Auriana, which was stationed there from 69 to the end of the 80s.